Does the Current Generation have Adequate Environmental Literacy? Case Study of Prospective Biology Teacher - Marlina, Reni; Hamdani; Siti Lathifah, Suci (Journal of Education Reseach and Evaluation, 2024)
From an environmental literacy perspective, prospective teachers need to have mastery of the domains of knowledge, attitudes, cognitive skills and behavior in teaching practice. This research aims to validate the environmental literacy of prospective biology teachers after learning micro teaching. The environmental literacy measurement instrument used is the Environmental Literacy Assessment of Micro Teaching (ELAMt) in the form of questions in the form of multiple choices and a questionnaire with a 4-point Likert scale. The instrument was given to 30 prospective biology teachers in experimental and control classes. This research uses a quasi-experimental method with a nonequivalent pretest-posttest control group design. There were 3 activities carried out, namely Focus Group Discussion (FGD), developing instruments, and environmental literacy measurements. The results of the research show that teaching practice in micro teaching has a big effect on increasing the environmental literacy of prospective biology teachers, especially in the domain of environmental literacy knowledge and cognitive skills. On the other hand, teaching training has not been able to significantly increase the domain of positive attitudes and behavior of prospective biology teachers towards the environment. So far, micro teaching has been more dominant in mastering teaching skills and less focused on the affective development of prospective biology teachers. The integration of environmental literacy in the teaching practices of prospective biology teachers is an implication of this research. Overall, it can be concluded that environmental literacy should be integrated into all courses so that can be ingrained in the daily lives of prospective biology teachers.